Elastisitas Permintaan dan Penawaran pada Komoditas Jeruk Lemon Lokal - Hawina Siti Alanasry; Lucky Safitri; Nur Azizah; Yolanika Cahyadi; Putri Imelda; Rasidin Karo Karo Sitepu (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the price elasticity of demand and supply of local lemon oranges in Indonesia, a key horticultural commodity. The data used are historical records of prices and demand in Sleman Regency (2003–2006), as well as consumption and supply in Medan City (2010–2011). The research adopts a quantitative approach using price elasticity analysis with the midpoint formula. The results show that demand is inelastic (Ed < 1), meaning that price changes do not significantly affect lemon demand. On the other hand, supply is elastic (Es > 1), indicating a strong producer response to price changes. These findings are essential for price-setting strategies, production increase planning, and managerial decision-making in maintaining the stability of local lemon supply and prices in the domestic market.